511. The cefazolin (CZ) and piperacillin-tazobactam (TZP) inoculum effects (IEs) are persistent amongst serial isolates of methicillin-sensitive Staphylococcus aureus (MSSA) derived from the sputum of persons with cystic fibrosis (pwCF) despite variation in other phenotypes. (15th December 2022) - Svishchuk, Julianna; Waddell, Barbara Jean M; Lee, Sicheng; Rabin, Harvey; Lisboa, Luiz; Gregson, Daniel; Surette, Michael; Parkins, Michael
Abstract: Background: Phenotypic diversity among chronically infecting pathogens within the airways of pwCF is increasingly recognized, limiting susceptibility testing-directed decision-making (Somayaji, 2019, JCF ). While it is an important outcome determinant in infection (Miller, 2018, OFID ), the IE has generally only been studied in acute infection models. Herein, we sought to establish if variation in the presence of the IE to beta-lactams exists among CF-derived MSSA. Methods: Single sputum cultures from 10 pwCF with chronic MSSA infection of ≥ 10 years in duration were collected, and 10 unique colonies from each were selected and confirmed as MSSA for a total of 100 isolates. Individual isolates were subjected to susceptibility testing at standard (SI: 10 5 CFU/mL) and high inoculum (HI: 10 7 CFU/mL) against CZ and TZP and assessed for protease (PRO) and hyaluronidase (HA) production in triplicate. The presence of the IE was defined if a ≥ 4-fold difference in MIC between SI and HI existed. All 100 strains were typed using pulsed-field gel electrophoresis. Results: Patients included had a median age of 30.5 years, forced vital capacity of 93%, forced expiratory volume in one second of 66% predicted, and a BMI of 21.5 kg/m 2 . Median sputum MSSA burden was 10 6 CFU/ml. The IE was overall more common with TZP than CZ: 47% vs 33%, respectively. Median MIC50 for CZ increased between SI and HI: 0.5 to 1µg/mL, and TZP: 2 to 4µg/mL (p< 0.0001 for both). The most prevalent pulsotypes identified corresponded to multilocus sequence types (ST)-5 (20%), ST-30 (15%), and ST-1 (5%), where ST-30 isolates were more likely to exhibit the CZ and TZP IE (p< 0.0001 for both). Eight out of 10 patients had all isolates belonging to the same pulsogroup. Of patients infected with a single strain, discordance between IE phenotype was not noted, though PRO and HA production varied. Among these patients, the standard deviation of zone clearance diameter ranged from 0-0.9cm (mean range: 0-1.4cm) and 0-1.8cm (mean range: 0-7.2cm), respectively, between individual isolates. Conclusion: Phenotypic diversity in chronic MSSA exists within the airways of pwCF. However, we observed the IE for CZ and TZP to be strain dependent, without variable penetrance. Disclosures: All Authors : No reported disclosures.